Taman Mini Indonesia Indah sebagai Bagian dari Fenomena Taman Budaya Dunia - Wulandari, Anak Agung Ayu (Bina Nusantara University, 2012)
Cultural display in an open space or known as cultural parks appears rapidly as a worldwide phenomenon. From the European model which has a strong educational value, to the Asian parks which not only has educational function, but also has recreational purposes. So many types and characteristics of these parks, researches give them different names, thodse are Open-air museums, Ethnographic Theme Parks or even Theme Parks. Taman Mini Indonesia Indah as a part of this phenomenon was built first and foremost for educational purposes, therefore Taman Mini can be considered as an open-air museum. However, since Taman Mini also has recreational purposes, others can argue that Taman Mini is a theme park. Qualitative method will be used for this research, through observation to Taman Mini Indonesia Indah, followed by extensive literature review. With these data along with a table which points out the distinction between museum and theme parks. It can be concluded that Taman Mini is a Theme Park.